2021
DOI: 10.1002/advs.202005047
|View full text |Cite
|
Sign up to set email alerts
|

CHAF1A Blocks Neuronal Differentiation and Promotes Neuroblastoma Oncogenesis via Metabolic Reprogramming

Abstract: Neuroblastoma (NB) arises from oncogenic disruption of neural crest (NC) differentiation. Treatment with retinoic acid (RA) to induce differentiation has improved survival in some NB patients, but not all patients respond, and most NBs eventually develop resistance to RA. Loss of the chromatin modifier chromatin assembly factor 1 subunit p150 (CHAF1A) promotes NB cell differentiation; however, the mechanism by which CHAF1A drives NB oncogenesis has remained unexplored. This study shows that CHAF1A gain-of-func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 86 publications
1
22
1
Order By: Relevance
“…This was consistent with the research nding that elevated expression of CHAF1A could promote thymidylate synthetase activity, leading to 5-FU resistance in gastric cancer [43]. In addition, it was reported that abnormally high expression of CHAF1A could affect the metabolic pathways of some amino acids, such as methionine, eventually inducing 5'-methylthioadenosine (MTA) accumulation in neuroblastoma [7]. Homozygous deletion of the methylthioadenosine phosphorylase (MTAP) is frequently found in human cancers, and the application of purine analogue has been shown to be effective therapeutic option in MTAP deletion cancer patients [44].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This was consistent with the research nding that elevated expression of CHAF1A could promote thymidylate synthetase activity, leading to 5-FU resistance in gastric cancer [43]. In addition, it was reported that abnormally high expression of CHAF1A could affect the metabolic pathways of some amino acids, such as methionine, eventually inducing 5'-methylthioadenosine (MTA) accumulation in neuroblastoma [7]. Homozygous deletion of the methylthioadenosine phosphorylase (MTAP) is frequently found in human cancers, and the application of purine analogue has been shown to be effective therapeutic option in MTAP deletion cancer patients [44].…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of genetic alterations was too low to lead cancers development and progression. Elevated expression of CHAF1A has been reported to be associated with several solid cancers [4,6,7,11,34], it was found that this phenomenon was commonly shared in more cancer types, indicating that abnormal higher expression of CHAF1A could be a potential biomarker for cancer diagnosis. Moreover, there was no study about the functional roles and mechanisms of CHAF1A in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al also demonstrated that CHAF1A overexpression facilitates cell proliferation, and inhibits apoptosis in human retinoblastoma cells [ 21 ]. Tao et al found that CHAF1A facilitates neuroblastoma oncogenesis and blocks neuronal differentiation through metabolic reprogramming [ 22 ]. Moreover, high levels of CHAF1A expression was found in GC tissue and cell lines, and the up-regulation of CHAF1A was found to be associated with poor clinical outcome [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines, including spermidine, spermine, and their precursor putrescine, are tightly regulated polycationic molecules that are broadly involved in cellular activities (Supplemental Figure 1; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.158457DS1) (1)(2)(3). Polyamine metabolic dysregulation has been intensively investigated in pathological conditions, including aging, cancers, and neurological and immunological diseases (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Gene mutations of polyamine pathway enzymes cause severe diseases (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%